2022
DOI: 10.1039/d2ta03062d
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia borane as an efficient direct fuel in alkaline fuel cells: mechanism, catalysts, applications, and challenges

Abstract: Ammonia borane (NH3BH3, AB) has attracted attention as carbon-free energy owing to its non-toxicity, excellent stability, and high solubility in water under ambient conditions. Unlike the traditional application as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…For the former method, Xu et al 85 prepared Ru NPs supported on XC-72 carbon via an adsorption-low temperature pyrolysis method. Specifically, the Ru 3 (CO) 12 precursor was first adsorbed in the porous carbon and then annealed at 300 1C to obtain the optimal Ru/C-300. It is found that this strategy facilitated the uniform confinement of Activated carbon.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the former method, Xu et al 85 prepared Ru NPs supported on XC-72 carbon via an adsorption-low temperature pyrolysis method. Specifically, the Ru 3 (CO) 12 precursor was first adsorbed in the porous carbon and then annealed at 300 1C to obtain the optimal Ru/C-300. It is found that this strategy facilitated the uniform confinement of Activated carbon.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…[6][7][8] Among the chemical hydrogen storage materials, ammonia borane-NH 3 BH 3 -(AB) has attracted intense attention due to its high hydrogen density (19.6 wt%), low molecular weight (30.7 g mol À1 ), long-term stability, high solubility in water and methanol, lack of toxicity and controllable hydrogen production. [9][10][11][12] With a white color appearance, AB is a solid crystal at room temperature with a density of 0.74 g cm À3 and a melting point of 112-114 1C. 13 The presence of the three protic N-H and three hydridic B-H hydrogens in AB leads to intra and intermolecular interactions, facilitating the release of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, when AB is employed for hydrogen generation, the generation process may result in undesirable byproducts, leading to resource wastage. 11 Therefore, the direct electrooxidation of AB stands out as a more attractive option for applications in fuel cells. The electrochemical mechanism underlying the direct electrooxidation of AB in alkaline conditions is as follows 12,13 :…”
Section: Introductionmentioning
confidence: 99%
“…AB holds potential utility in fuel cells as a hydrogen‐generation material or as a substrate for direct electrooxidation 7–10 . However, when AB is employed for hydrogen generation, the generation process may result in undesirable byproducts, leading to resource wastage 11 . Therefore, the direct electrooxidation of AB stands out as a more attractive option for applications in fuel cells.…”
Section: Introductionmentioning
confidence: 99%